Sudden Deaths: Taking Stock of Geographic Ties - Faccio, Mara; Parsley, David C. (Journal of Financial and Quantitative Analysis, 2009)
Abstract Analysis of a worldwide sample of sudden deaths of politicians reveals a market-adjusted 1.7% decline in the value of companies headquartered in the politician's hometown. The decline in value is followed by a drop in the rate of growth in sales and access to credit. Our results are particularly pronounced for family firms, firms with high growth prospects, firms in industries over which the politician has jurisdiction, and firms headquartered in highly corrupt countries.